Update on the current recommendations and outcomes in pregnant women with antiphospholipid syndrome. (November 2014) - Chighizola, Cecilia Beatrice; Gerosa, Maria; Trespidi, Laura; Di Giacomo, Alessio; Rossi, Federica; Acaia, Barbara; Meroni, Pier Luigi
<x xml:space="preserve">Abstract</x> Pregnancy morbidity is part of the clinical spectrum of the antiphospholipid syndrome (APS), a chronic autoimmune condition serologically characterized by the persistent positivity of antiphospholipid antibodies (aPL). Antiplatelet and anticoagulant agents are the mainstay of the treatment of obstetric APS. However, there is an ongoing debate about the optimal management of women with most severe aPL-mediated obstetric complications, women not fulfilling APS criteria and those with refractory disease. Unfortunately, the literature cannot provide definite answers to these controversial issues, being flawed by many limitations. The evidence supporting the recommended therapeutic management of different aPL-related obstetrical clinical manifestations is presented, with a critical appraisal of each approach.